Molecular imaging and molecular guided Therapy - Lerch, H.; Jigalin, A. (Nuklearmedizin - NuclearMedicine, 2006)
Aim and method: Scientific publications in the journal of Nuklearmedizin Molecular Imaging and Therapy during 2004/2005 were retrospectively examined for their potential classification to molecular imaging or molecular guided therapy, functional imaging and therapy, and were compared to earlier analyses. Results: Of the 57 original papers examined, 36 (63%) were assigned to the category of molecular imaging / molecular guided therapy. Within this category, the number of original papers on molecular guided therapy increased by 19% compared to preceding periods. There was a general overall increase in the proportion of experimental papers and more frequent inclusion of basic background subjects. Conclusion: The development of molecular imaging as a direct instrument in therapy planning leads to further promotion of molecular guided therapy. The structural advantage of nuclear medicine, uniting method-lead diagnosis and therapy within one specialist subject, predestines it to advance molecular imaging and molecular guided therapy.
Keywords: Molecular imaging; molecular guided therapy; nuclear medicine